Imigrantes e refugiados venezuelanos na paraíba: aspectos para o desenvolvimento da política migratória em nível local - Torres, Raissa Brindeiro De Araújo (2019)
The migratory phenomenon goes through the long way of evolution of society, being noticed from the time of the great colonization, going through the industrial period and of great economic advance, until the most recent scenario in which it lives. This research deals more specifically with immigrants (including stateless persons) and refugees, the two largest groups having the highest incidence of international migratory flows to Brazil, taking as a sample the most recent population displacement of Venezuelans to the country. The theme is relevant, considering that the relations between the different peoples are increasingly complex, in the middle of the interconnected world, not only by the ease of transport and communication, but above all by the breadth of the reflexes resulting from human interactions, which permeate aspects economic, social, political and cultural, making themselves felt in different forms and degrees of intensity throughout the international society. Research seeks to better understand the international migratory phenomenon and to identify the real advances in the defense of the human rights of immigrants and refugees, as well as to recognize the gaps or deficiencies in their treatment. Having as its object of study the flow of Venezuelan immigrants and refugees to Paraíba, through the process of internalization, the research proposes the creation of a migratory policy at local level that can meet the needs of Venezuelans living in the State, ensuring full satisfaction of their rights. The problem is to know how Brazil has responded to the recent international migratory flow of Venezuelans, considering the binding rules of international law and those of its own legal order, especially with regard to Article 4 of the 1988 Federal Constitution. As a hypothesis, Brazil still faces difficulties in dealing with international migration flows, despite the advances experienced in relation to the legal rules that instituted the new Migration Law, and there is no National Policy on Migration, Refuge and Statelessness, due to the lack of regulation of the art. 120 of Law no. 13.445/2017, which demonstrates the weakness in articulating interdependent migration policies between the three spheres of power. In this sense, the debate on the protection of immigrants and refugees in Brazil reflects on the construction of a new conception of citizenship, with a broad, inclusive and solidary perspective, in view of the human interactions provided by international migrations and the need to guarantee human rights of migrants. The methods of historical and monographic procedure and the techniques of bibliographic and documentary research are used. The nature of the methodological aspect is qualitative and quantitative, seeking to better understand the migratory phenomenon, in order to identify the challenges to be faced regarding the guarantee of human rights. RESUMEN El fenómeno migratorio recorre el largo camino de la evolución de la sociedad, percibiéndose desde la época de las grandes colonizaciones, pasando por el período industrial y de gran avance económico, hasta el escenario más reciente en el que vive. Esta investigación trata más específicamente con los inmigrantes (incluidas las personas apátridas aquí) y los refugiados, siendo los dos grupos principales con la mayor incidencia en los flujos migratorios internacionales a Brasil, tomando como muestra el desplazamiento de población de venezolanos más reciente al país. El tema es relevante, considerando que las relaciones entre los diferentes pueblos son cada vez más complejas, en medio del mundo interconectado, no solo por la facilidad de transporte y comunicación, sino sobre todo por la amplitud de los reflejos resultantes de las interacciones humanas, que impregnan aspectos económica, social, política y cultural, haciéndose sentir de diferentes maneras y grados de intensidad en toda la sociedad internacional. La investigación busca comprender mejor el fenómeno migratorio internacional e identificar los avances reales en la defensa de los derechos humanos de los inmigrantes y refugiados, así como reconocer las lagunas o deficiencias en su tratamiento. Teniendo como objeto de estudio el flujo de inmigrantes y refugiados venezolanos a Paraíba, a través del proceso de internalización, la investigación propone la creación de una política migratoria local que pueda satisfacer las necesidades de los venezolanos que viven en el Estado, asegurando plena satisfacción de sus derechos. El problema es cómo ha respondido Brasil al reciente flujo migratorio internacional de venezolanos, considerando las normas vinculantes del derecho internacional y las de su propio sistema legal, especialmente con respecto al Artículo 4 de la Constitución Federal de 1988. Brasil aún enfrenta dificultades para lidiar con los flujos migratorios internacionales, a pesar de los avances experimentados en relación con las normas legales que instituyeron la nueva Ley de Migración, y no existe una Política Nacional sobre Migración, Refugio y Apatridia, debido a la falta de regulación del art. 120 de la Ley n. 13.445/2017, lo que demuestra la fragilidad en la articulación de políticas migratorias interdependientes entre las tres esferas de poder. En este sentido, el debate sobre la protección de inmigrantes y refugiados en Brasil se refleja en la construcción de una nueva concepción de ciudadanía, con una perspectiva amplia, inclusiva y solidaria, en vista de las interacciones humanas proporcionadas por las migraciones internacionales y la necesidad de garantizar los derechos. derechos humanos de los migrantes. Se utilizan los métodos de procedimiento histórico y monográfico y las técnicas de investigación bibliográfica y documental. La naturaleza del aspecto metodológico es cualitativa y cuantitativa, buscando comprender mejor el fenómeno migratorio, de modo que se identifiquen los desafíos que deben enfrentarse con respecto a la garantía de los derechos humanos.